Coevaporation of Doped Inorganic Carrier‐Selective Layers for High‐Performance Inverted Planar Perovskite Solar Cells. Issue 7 (22nd March 2022) - Jiang, Jiexuan; Mavrič, Andraž; Pastukhova, Nadiia; Valant, Matjaz; Zeng, Qiugui; Fan, Zeyu; Zhang, Beibei; Li, Yanbo
Abstract : Inorganic carrier‐selective layers (CSLs), whose conductivity can be effectively tuned by doping, offer low‐cost and stable alternatives for their organic counterparts in perovskite solar cells (PSCs). Herein, a dual‐source electron‐beam co‐evaporation method for the controlled deposition of copper‐doped nickel oxide (Cu:NiO) and tungsten‐doped niobium oxide (W:Nb2 O5 ) as hole and electron transport layers, respectively, is used. The mechanisms for the improved conductivity using dopants are investigated. Owing to the improved conductivity and optimized band alignment of the doped CSLs, the all‐inorganic‐CSLs‐based PSCs achieve a maximum power conversion efficiency (PCE) of 20.47%. Furthermore, a thin titanium buffer layer is inserted between W:Nb2 O5 and the silver electrode to prevent halide ingression and improve band alignment. This leads to a further improvement of PCE to 21.32% and long‐term stability (1200 h) after encapsulation. Finally, the large‐scale applicability of the doped CSLs by coevaporation is demonstrated for the device with 1 cm 2 area showing a PCE of over 19%. The results demonstrate the potential application of the coevaporated CSLs with controlled doping in PSCs for commercialization. Abstract : A dual‐source electron beam coevaporation method is used for the controlled deposition of copper‐doped nickel oxide and tungsten‐doped niobium oxide as hole and electron transport layers, respectively. Perovskite solar cells based on these inorganic carrier‐selective layers achieve power conversion efficiencies of 21.32% for a 0.155 cm 2 device and 19.01% for a 1 cm 2 device.